2014
DOI: 10.1021/ie502384g
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Plasma Effect on Cotton Nonwovens

Abstract: The possibility of using atmospheric pressure plasma treatment (APT) without any additional functionalizing chemicals as an environmentally friendly technique for processing cotton nonwovens has been investigated. The quantitative determination of waxes suggested that APT results in the removal of waxes from cotton nonwovens and consequently increases its hydrophilicity. Fourier transform infrared studies showed that APT was capable of removing wax covering individual layers of cotton fibers. Intense plasma tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
0
3
1
Order By: Relevance
“…In this work, we explored both long (30 min, 60 min, and 90 min) and short (15 min) plasma exposure times at a high power density of 0.46 W/cm 2 on cotton yarn samples. Other researchers have observed slight degradation of cotton fabrics using atmospheric pressure plasma treatments with exposure times less than or equal to 30 min [12][13][14]; we found, however, longer plasma exposure times greater than 30 min with a power density of 0.46W/cm 2 to cause significant degradation of both greige and scoured cellulose yarn. The time to significant degradation in this study was relatively long, however, degradation should occur at shorter plasma exposure times if a higher power density unit is implemented.…”
Section: Introductioncontrasting
confidence: 72%
“…In this work, we explored both long (30 min, 60 min, and 90 min) and short (15 min) plasma exposure times at a high power density of 0.46 W/cm 2 on cotton yarn samples. Other researchers have observed slight degradation of cotton fabrics using atmospheric pressure plasma treatments with exposure times less than or equal to 30 min [12][13][14]; we found, however, longer plasma exposure times greater than 30 min with a power density of 0.46W/cm 2 to cause significant degradation of both greige and scoured cellulose yarn. The time to significant degradation in this study was relatively long, however, degradation should occur at shorter plasma exposure times if a higher power density unit is implemented.…”
Section: Introductioncontrasting
confidence: 72%
“…Jinka et al 152 studied the use of atmospheric pressure plasma treatment (APT) for the processing of cotton nonwoven fabrics and found that APT could be a viable alternative to caustic soda for dewaxing cotton. Fourier transform infrared (FT-IR) spectra revealed diminishing peak intensities particularly in the region between 3000 and 2800 cm −1 after plasma treatment which confirmed that plasma had a strong influence on the dewaxing of nonwoven cotton (Figure 9).…”
Section: Industrial and Engineering Chemistry Researchmentioning
confidence: 99%
“…FTIR spectra of untreated (black line), Plasma I treated (red line), and Plasma II treated (blue line) cotton nonwoven fabrics in the regions of 1800–800 cm –1 (top) and 3500–2600 cm –1 (bottom). Data are based on Jinka et al …”
Section: Irradiation Technologiesmentioning
confidence: 99%
“…To accompany our latest additions, we have curated a list of past publications within the scope of chemical engineering under extreme conditions. These manuscripts address topics such as how to conduct thermogravimetric measurements at temperatures found close to the surface of the sun, synthesizing tetramine at extreme temperatures and pressures, extreme thermophilic fermentation, dissolution of calcite at 1450 bar, kinetic analysis of disinfectants in supercritical water, antiwear films for steel coatings under extreme temperatures and pressures, plasma treatment of cotton nonwovens, extreme shearing for cheese production, extreme liquid natural gas pool fires, freeze-resistant smart windows, storage stability of emulsion under extreme conditions, oil spill remediation under extreme aquatic conditions (pH and salinity), fermentation of microalgae under extreme alkaline conditions, metal–organic framework (MOF) clothing for chemical warfare protection, microstructures to enhance freezing under electric fields, thermally stable electrolytes, and electromagnetic shielding materials under harsh weathering conditions …”
mentioning
confidence: 99%